Crafting Lives: Experiences of Ethiopian Refugees in Cairo - Abd El-Megid, Nayrose S. (AUC Knowledge Fountain, 2024)
There has been an ongoing influx of refugees for years driven by political instability, famine, and prolonged conflicts in the region, leading many individuals to seek sanctuary in other countries. Egypt has become a host country for many years, whether for settlement or transit, for various populations from different nationalities hoping to find refuge. However, amidst this influx, Ethiopian refugees often find themselves overlooked or usually associated on the sidelines with other African nationalities; their stories and struggles are marginalized in broader narratives of displacement. The experience of Ethiopians is heterogeneous and multidimensional in terms of their intersectional identities of being a refugee, black, men or women, and discriminated against in the Egyptian milieu due to the Grand Ethiopian Renaissance Dam (GERD) crises. This is also triggered by an acute economic and legal situation, making living conditions for vulnerable populations worsen due to dramatic price hikes and uncertainty. This thesis delves into the lived experiences of Ethiopian refugees in Cairo, specifically Oromo, focusing on their intersectional identities and the unique dynamics they navigate. The research traces the historical trajectories of the Ethiopian diaspora, examines labor dilemmas, and explores the confluence of identity axes in shaping their experiences and opportunities. Through a refugee-centered lens, the study analyzes how migration impacts and reshapes identity categorizations, and how Oromo in Egypt cope with these shifts in the face of the generalized disadvantaged position of victimization. By employing intersectionality as a guiding framework, the paper sheds light on the challenges Oromo Ethiopian refugees face in Egypt and the strategies they utilize to craft a life in such informality and liminality. Going beyond the mere ‘integration’ and nullifying the confines of the formal versus informal myopic dichotomy, labor as a nexus for accessing other needs and securing livelihoods will be a point of departure. Additionally, the role and dynamics of other entities in supporting the refugee community is explored. Through a detailed analysis of these themes, the research aims to contribute to a deeper understanding of the complexities of refugees’ experiences in Egypt and the broader implications for gender and refugee interdisciplinary studies.